Distribution of HLA specificity in patients with acute lymphoblastic leukemia - Burkitbayev, Zh.K.; Ramilyeva, I.R.; Turganbekova, A.A.; Zhiburt, E.B. (Онкологія, 2018)
Aim: to study the characteristics of the HLA phenotype in patients with acute lymphoblastic leukemia (ALL) in Kazakhstan, to search for the relationship between the development of ALL and the expression of HLA antigens. Objects and methods: 3621 healthy donors and 261 patients with a diagnosis of ALL were examined. All patients were on treatment at the clinic of the National Scientific Center of Oncology and Transplantology in Astana and were diagnosed on the basis of the ALL-2013KZ protocol (Minutes No. 16 of August 16, 2013). DNA was isolated from peripheral blood leukocytes by a proteinase method using the PROTRANS DNA BOX reagent kit (Protrans, Germany). Typing of HLA antigens (HLA-A, B, C, DRB1, DQB1) was performed by polymerase chain reaction. The results were assessed using the descriptive statistics methods. Results: a study of the distribution of HLA antigens in patients with ALL and healthy donors suggested the existence of associative links between the presence of HLA-A*30, B*44, C*16, DRB1*07, *16 and the development of this pathology. Persons having phenotype antigens HLA-A*02, C*02, DQB1*06 are resistant to the onset of this disease. Conclusion: the obtained data can be used in the development of immunogenetic criteria for predicting the development of ALL and the study of various diseases associated with HLA antigens.